2018
DOI: 10.1002/1878-0261.12414
|View full text |Cite
|
Sign up to set email alerts
|

Targeting HER2 in patient‐derived xenograft ovarian cancer models sensitizes tumors to chemotherapy

Abstract: Ovarian cancer is the most lethal gynecologic malignancy. About 75% of ovarian cancer patients relapse and/or develop chemo‐resistant disease after initial response to standard‐of‐care treatment with platinum‐based therapies. HER2 amplifications and overexpression in ovarian cancer are reported to vary, and responses to HER2 inhibitors have been poor. Next generation sequencing technologies in conjunction with testing using patient‐derived xenografts (PDX) allow validation of personalized treatments. Using a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 95 publications
0
20
0
Order By: Relevance
“…Hedgehog pathway, upregulated in a subset of OC [58], was also targeted with a specific inhibitor, leading to significant decrease of tumor volume in OC PDX [59]. More recently, combinatorial therapy including both chemotherapeutic agents and HER2 inhibitors was evaluated on OC PDX [60]. Furthermore, tumorigenicity as xenografts per se proved to be inversely correlated with progression-free survival [61].…”
Section: Patient-derived Xenografts (Pdxs)mentioning
confidence: 99%
“…Hedgehog pathway, upregulated in a subset of OC [58], was also targeted with a specific inhibitor, leading to significant decrease of tumor volume in OC PDX [59]. More recently, combinatorial therapy including both chemotherapeutic agents and HER2 inhibitors was evaluated on OC PDX [60]. Furthermore, tumorigenicity as xenografts per se proved to be inversely correlated with progression-free survival [61].…”
Section: Patient-derived Xenografts (Pdxs)mentioning
confidence: 99%
“…Therefore, more effective targeted-therapy strategies for HER2-positive cancers are necessary to overcome the limitation of trastuzumab in efficacy. Harris et al found that single-agent trastuzumab results in a limited treatment benefit in ovarian cancers; however, a combination therapy including both chemotherapy drugs and HER2-targeted antibody provides a far better response [ 43 ]. Many studies have also indicated that new combinatorial regimens of trastuzumab with other antibodies or small-molecule inhibitors may contribute to enhance the efficacy of trastuzumab and overcome trastuzumab resistance [ 9 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…PDX model has become an effective tool to evaluate anti-tumor drugs and conduct research on personalized cancer treatment. 25,26 In this study, we established two bladder cancer PDX models, one of which has multi-organ metastasis potential. H&E staining and IHC analysis conrmed that the xenogra tumor well retained the pathological features of the primary tumor.…”
Section: Discussionmentioning
confidence: 99%